Policy options for accelerated growth and competitiveness of the domestic rice economy in Nigeria - Johnson, Michael E.; Takeshima, Hiroyuki; Gyimah-Brempong, Kwabena; Kuku-Shittu, Oluyemisi (International Food Policy Research Institute, 2013)
The Nigerian government has embarked on an ambitious plan to make the country self-sufficient in rice production by 2015 under its current Agricultural Transformation Agenda (ATA). The plan is in response to the perceived threat to the Nigerian economy of larger volumes of milled rice imports into Nigeria, with an import bill currently exceeding US$2 billion. To reverse the growing trend in rice imports, the Nigerian government has introduced a number of key policies and investment strategies to increase domestic rice production and improve its competitiveness with imports. This is being done through a combination of import restrictions, input policy and institutional reforms, and direct investments along the rice value chain. However, little is known as to whether this ambitious short term goal can be achieved and what would be needed over the long term to sustain increased production. This policy note synthe-sizes the results of various analyses assessing the potential for Nigeria to transform its domestic rice sector to become competitive with imports. A number of key messages emerge: (1) import restrictions alone are insufficient because they are costly to implement and likely to be ineffective; (2) given agro-ecological conditions and biophysical potential, current rice technologies, and farmer characteristics, short term increases in rice production are unlikely to meet domestic demand; (3) sufficient support to small-to-medium scale rice pro-cessers to improve quality will be even more important than promoting large-scale milling technologies; and, (4) a combination of rice production technology growth and market improvement are fundamental prerequisites for raising rice self-reliance without hurting the overall economy.